Peningkatan Baca Alqur’an di TPQ Al-Anwar Dusun Siderejo Desa Wandanpuro - Isnan Murdiansyah (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
TPQ Al-Anwar Wandanpuro experiences several obstacles in teaching and learning activities to read and write the Qur'an, this causes a problem that hinders the occurrence of a goal to be achieved so it is necessary, community service activities in the KKM scheme are carried out to increase reading the Qur'an in TPQ Al-Qnwar Wandanpuro. The purpose of KKM activities is to improve the ability and understanding of TPQ Al-Anwar Wandanpuro teachers to the implementation of learning using the tilawati method. Helping to improve understanding of tajwid material and its practice for TPQ Al-Anwar Wandanpuro students. As well as improving and developing the abilities of TPQ Al-Anwar teachers in delivering learning materials to read Al-Quran that are not boring and easy to understand. The results of KKM activities are to provide additional insight and knowledge and skills to the teaching staff at TPQ Al-Anwar Wandanpuro Hamlet. Fostering enthusiasm and enthusiasm for student learning in an effort to improve the ability to read Al-Qur'an by delivering various tajwid materials and practicing little by little tajwid knowledge and remain in accordance with the tilawati method. As well as helping the TPQ Al-Anwar Wandanpuro to get facilities for supporting activities for learning to read Al-Qur'an.